Daniel Guggenheim Fund for the Promotion of Aeronautics records - Daniel Guggenheim Fund for the Promotion of Aeronautics
Correspondence, reports, articles, pamphlets, legal and financial records, printed matter, and other records relating chiefly to commercial aviation in the United States and to a history of the fund written by R.H. Mayo. Subjects include aeronautical education and research, aviation safety, technical development, use of aviation for passenger travel and transport of freight, and Charles A. Lindbergh's tour of the U.S. in 1927. Includes material pertaining to aeronautical research at universities such as the California Institute of Technology and Massachusetts Institute of Technology. Correspondents include Hutchinson Ingham Cone, Harry Frank Guggenheim, Emory Scott Land, Aero-Club von Deutschland, Associazione italiana di aerotecnica, and the Royal Aeronautical Society, England.
Fund established to facilitate technical development, improve safety, and expand the popularity of aviation. Active from 1926 to 1930.
Collection material in English and German.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Cone, Hutchinson Ingham, -- 1871-1941 -- Correspondence; Guggenheim, Daniel, -- 1856-1930.; Guggenheim, Harry Frank, -- 1890-1971 -- Correspondence; Land, Emory Scott, -- 1879-1971 -- Correspondence; Lindbergh, Charles A. -- 1902-1974.; Mayo, R. H. -- 1890-; Aero-Club von Deutschland -- Correspondence; Associazione italiana di aerotecnica -- Correspondence; California Institute of Technology; Massachusetts Institute of Technology; Royal Aeronautical Society -- Correspondence; Aeronautics; Aeronautics -- Endowments; Aeronautics -- Research; Aeronautics -- Safety measures; Aeronautics -- Societies, etc; Aeronautics -- Study and teaching; Aeronautics, Commercial -- Freight; Aeronautics, Commercial -- Passenger traffic; Aeronautics, Commercial -- United States; Air travel -- United States